The moderating role of positive education to the relationship of level of anxiety and academic achievement in mathematics - C. Arenas, Joel; Paul N. Cabotaje, John; Margarita A. Agao-agao, Ana; D. Samson, Consuelo; A. Sam, Solayha (Edelweiss Applied Science and Technology, 2024)
Positive education emphasizes the study of happiness and well-being to encourage and support students, teachers, schools, and communities in their growth and development. The primary goals are to lower anxiety levels, boost life satisfaction, and improve students’ academic performance. This study employed an experimental research design aimed at analyzing the post-test results of positive education in the level of anxiety and academic achievement in mathematics through moderated hierarchical multiple regression analysis. Findings showed that students’ anxiety level negatively affected their mathematics academic achievement. Positive education, on the other hand, demonstrated a significant effect on the mathematical achievement of the experimental group. Positive education significantly moderated the relationship between anxiety level and mathematics academic achievement. A test of simple slopes for post-test results revealed that the relationship between anxiety level and academic achievement was significant in the experimental group, but it was not significant in the control group. These results imply that positive education intervention serves as an effective strategy for enhancing mathematics teaching.